214k views
4 votes
Make t the subject of the formula.
u = v+ 2t​

2 Answers

4 votes

Answer:


u = v + 2t \\ u - v = 2t \\ t = ((u - v))/(2)

t=(u-v)/2 is the right answer.

User Musa
by
5.5k points
12 votes

9514 1404 393

Answer:

t = (u -v)/2

Explanation:

Observe what is done to t:

  • multiplied by 2
  • v added to the product

Undo these operations, starting with the last one and working up the list.


u = v+2t \qquad\text{given}\\\\u-v=2t \qquad\text{undo addition by subtracting $v$}\\\\(u-v)/(2)=t \qquad\text{undo multiplication by dividing by 2}\\\\\boxed{t=(u-v)/(2)}

User Ilya Popov
by
5.1k points